Sacred precincts : the religious architecture of non-Muslim communities across the Islamic world - Gharipour, Mohammad; Guidetti, Mattia (Arts and archaeology of the Islamic world., 2014)
Sacred Precincts examines non-Muslim religious sites in the Islamic world, revealing how architecture responds to contextual issues and traditions. It explores urban contexts; issues of identity; design; construction; transformation and the history of sacred sites in the Middle East and Africa from the advent of Islam to the 20th century. The book includes case studies on churches, synagogues and sacred sites in Iran; Turkey; Cyprus; Egypt; Iraq; Tunisia; Morocco; Malta; Nigeria; Mali, and the Gambia.